Distributional Implications of Government Guarantees in Mortgage Markets - Gete, Pedro; Zecchetto, Franco (Oxford University Press, 2017)
We analyze the removal of the credit-risk guarantees provided by the government-sponsored enterprises (GSEs) in a model with agents heterogeneous in income and house price risk. We find that wealth inequality increases, driven by higher mortgage spreads and housing rents. Housing holdings become more concentrated. Foreclosures fall. The removal benefits high-income households, while hurting low- and mid-income households (renters and highly leveraged mortgagors with conforming loans). GSE reform requires compensating transfers, sufficiently high elasticity of rental supply, or linking GSE reform with the elimination of the mortgage interest deduction.
Keywords: E-51 Money Supply; Credit; G21- Banks; Depository Institutions; Micro Finance Institutions; Loan Guarantees; Credits; Grants; 53 Ciencias Económicas::5309 Organización de la industrial y política económica pública::5309.04 Estructura del mercado; ODS 1 - Fin de la pobreza; ODS 10 - Reducción de las desigualdades